Perception of change and ethical issues in the use of information and communication technologies in the health sector: Results of an online survey - Alaoui, Nissrine Hassini; Belouali, Saida (International Multidisciplinary Research Journal, 2020)
For several decades, information and communication technologies (ICT) applied to health have undergone a revolutionary development, whether they are e-health, telemedicine or others, these digital changes have marked the global care system. Today, internet is the common source of information to many uses, and it is considered as the wealthiest mine of information for any kind including those of health. This survey, which interviews both Moroccan practitioners and users, is conducted online by distributing two questionnaires. The aim of this study is to discover the perception that Moroccan doctors and users have concerning the change ICTs have been able to bring about without neglecting the ethical and deontological issues involved. The results showed that doctors are already using the web in their daily practice and are open to eHealth practices such as telemedicine. As for users, the practices of eHealth are an asset that should become more widespread. Further research is needed to confirm and further explore the results of this study.